Various Factors in Stunting Children Aged 12 to 60 Months - Suriani Rauf; Hendrayati Hendrayati (Humanistic Network for Science and Technology (HNST), 2019)
Stunting is a chronic nutritional problems caused by the low intake of nutrients in long term, resulting in unfulfilled demand for nutrients. Indonesia has the highest incidence of stunting compared to other Southeast Asian countries. The prevalence of stunting in Indonesia tends to increase. Basic medical research showed prevalence of stunting were 35.6% in 2010 and 37.2% in 2013. This study aimed to analyze determining factors in the incidence of stunting in children aged 12 to 60 months. The method used in this study was analytic survey with sample size as many as 155 stunting children. Determining factors in the incidence of stunting in children aged 12 to 60 months were intake of energy and macro-nutrients such as carbohydrates, proteins as well as fats. While the intake of micronutrients that contributed to the incidence of stunting were the intake of vitamin A and zinc. Beside the intakes, feeding practices such as consistency, frequency and habit of having breakfast were also determining factors in the incidence of stunting. Maternal knowledge concerning to nutrition, exclusive breastfeeding and complementary foods were not determining factor in the incidence of stunting but were the protective one. Keywords: feeding practices; nutritional intake; nutritional knowledge; stunting